2022
DOI: 10.1007/s40123-022-00560-5
|View full text |Cite
|
Sign up to set email alerts
|

Issues Revisited: Shifts in Binocular Balance Depend on the Deprivation Duration in Normal and Amblyopic Adults

Abstract: Introduction:Recent studies indicate that short-term monocular deprivation increases the deprived eye's contribution to binocular fusion in both adults with normal vision and amblyopia. In this study, we investigated whether the changes in visual plasticity depended on the duration of deprivation in normal and amblyopic adults. Methods: Twelve anisometropia amblyopic observers (aged 24.8 ± 2.3 years) and 12 agematched normal observers (aged 23.9 ± 1.2 years) participated in the study. The non-dominant eye of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Second, the psychophysical task that is used in the study might not have been sensitive enough to capture the boost in plasticity in amblyopia. In fact, previous studies show that the boost of plasticity from an increased patching duration was only present in one visual task but not another that measures binocular combination (Min et al, 2018(Min et al, , 2022. Lastly, it is well established that plasticity is markedly reduced in adults.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, the psychophysical task that is used in the study might not have been sensitive enough to capture the boost in plasticity in amblyopia. In fact, previous studies show that the boost of plasticity from an increased patching duration was only present in one visual task but not another that measures binocular combination (Min et al, 2018(Min et al, , 2022. Lastly, it is well established that plasticity is markedly reduced in adults.…”
Section: Discussionmentioning
confidence: 97%
“…There are several possibilities for why this was. First, the shift in eye balance after monocular deprivation has been shown to be smaller in amblyopes than that in normal observers (Min et al., 2022). To illustrate, 5 h patching induces a larger shift in eye balance in binocular combination than 2 h patching in normal but not in amblyopic observers.…”
Section: Discussionmentioning
confidence: 99%
“…At the time, these results suggest that there might be long-term changes in the suppressive interactions induced by short-term monocular deprivation in amblyopes, which might result from the larger plasticity in the amblyopic visual system. 59 More recently, the results from Min et al 60 and Zhou et al 44 show the sensory eye dominance returned to baseline in participants with normal vision, while the shifts in sensory eye dominance lasted more than 1 hour after the removal of the patch in amblyopic adults. Indeed, recent studies have observed improvements in both binocular (e.g., ocular dominance and stereopsis) and monocular (e.g., visual acuity) functions in older children and adults after successive daily inverse patching 2 hours/day for 2 months.…”
Section: Discussionmentioning
confidence: 98%
“…The changes after contrast deprivation is orientationally tuned ( Zhang et al, 2009 ), while monocular deprivation is not ( Zhou et al, 2014 ; Wang et al, 2017 ). Furthermore, the effect of the duration of adaptation seems to be uniquely different between contrast adaptation and monocular deprivation ( Min et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%